Insight into the role of solvents in enhancing hydrogen production: Ru-Co nanoparticles catalyzed sodium borohydride dehydrogenation - Filiz, Bilge Coskuner; Figen, Aysel Kanturk (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Ru-Co nanoparticles prepared in nano-size by combustion derived of citric acid used solgel technique followed by calcination process at 450 degrees C. The external and internal properties of nano-sized catalyst were characterized by XRD, XPS, SEM, TEM, ICP-OES, and N-2 sorption techniques. The characterization results proved that nano-sized catalyst was mixture of cubic Co3O4 (18 nm) and tetragonal RuO2 (40 nm) crystals with mesoporous structure (12.64 m(2)g(-1)). Insight into the role of solvents for enhancing hydrogen production from Ru-Co nanoparticles catalyzed sodium borohydride (NaBH4, SBH) was systematically studied by altering the dehydrogenation medium with water or methanol. The reaction kinetic performance of nano-sized catalyst was evaluated by performing both hydrogen generation reactions at various reaction temperatures, initial SBH concentration, and catalyst dosage to evaluate the hydrogen generation activity. Ru-Co nanoparticles exhibited exclusive catalytic performance for hydrogen generation by hydrolysis and methanolysis of SBH. The apparent activation energies (E-a) for the catalytic hydrolysis and methanolysis of SBH over Ru-Co nanoparticles were determined to be 20.02 kJ mol(-1) and 54.38 kJ mol(-1), respectively. Furthermore, Ru-Co nanoparticles also performed satisfied stability for both hydrolysis and methanolysis reactions. Beside both hydrogen generation was achived with fully conversion of SBH, Ru-Co nanoparticles promised good recyclability for at least 5 cycle for methanolysis of SBH. (C) 2019 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen; Nanoparticle; Catalyst; Hydrolysis; Methanolysis; AMMONIA BORANE; HYDROLYTIC DEHYDROGENATION; NABH4 HYDROLYSIS; EFFICIENT CATALYST; H-2 GENERATION; NANOWIRES; GRAPHENE; Chemistry; Electrochemistry; Energy & Fuels